Empowerment of Junior High School Digital School Teachers in Kartasura on Making E-Modules (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The use of unlimited computing power and data makes everything borderless and digital technology towards the era of reform 5.0. The purpose of the study was to find out how teacher empowerment at SMP Muhammadiyah Al-Kautsar Kartasura Special Program is in making E-modules for digital classes. This type of research is qualitative-descriptive. Research methods with documentation, interviews, and documentation. Data analysis with The results showed that the empowerment of teachers in the creation and development of E-modules carried out by SMP Muhammadiyah Al-Kautsar Kartasura Special Program is by providing workshops on making E-modules and using the Flip PDF Professional Application and forming a special team for ICT assisted by the curriculum section at school in coordinating the obstacles that occur in learning using E-modules for digital classes and ICT becomes an additional subject in digital classes. Efforts to empower teachers themselves are by holding discussions between subject-associated friends often held by teachers in filling out plotting, and creativity for the creation and development of E-modules so that the continuity of material from classes VII, VIII, IX.